2021
DOI: 10.4018/ijissc.2021040101
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment Analysis Using Machine Learning Algorithms and Text Mining to Detect Symptoms of Mental Difficulties Over Social Media

Abstract: A recent British study of people between the ages of 14 and 35 has shown that social media has a negative impact on mental health. The purpose of the paper is to detect people with mental disorders' behavior in social media in order to help Twitter users in overcoming their mental health problems such as anxiety, phobia, depression, paranoia, etc. For this, the author used text mining and machine learning algorithms (naïve Bayes, k-nearest neighbours) to analyse tweets. The obtained results were validated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In (Bouarara, 2022), the authors considered the main goal of their research to identify the behavior of people suffering from mental problems among Twitter users in order to support them. For this purpose, they have used text mining strategy relying on machine learning techniques such as naïve Bayes and knearest neighbours.…”
Section: Previous Workmentioning
confidence: 99%
“…In (Bouarara, 2022), the authors considered the main goal of their research to identify the behavior of people suffering from mental problems among Twitter users in order to support them. For this purpose, they have used text mining strategy relying on machine learning techniques such as naïve Bayes and knearest neighbours.…”
Section: Previous Workmentioning
confidence: 99%
“…e theory of machine learning is constantly evolving, which has led to an increase in the number of academics who are applying machine learning algorithms to the study of sentiment recognition of university online public opinion. ese scholars have found that their efforts have been fruitful [4,5]. An opinion evolution system model based on complex agent networks was constructed by the literature [6] in order to analyze the influence of various factors within the model on the development of public opinion.…”
Section: Introductionmentioning
confidence: 99%
“…Although these methods perform well in terms of classification accuracy, they still face many difficulties. The emotion dictionary-based approach, which takes the emotion dictionary as the main basis for judging and commenting on emotion polarity [3], relies on a large amount of manual intervention, such as dictionary construction and judgment rule formulation, etc. It is difficult to cope with the emergence of new and unknown words and has the domain dependence problem [4].…”
Section: Introductionmentioning
confidence: 99%